Exception, symbolism and compromise: the resilience of treason as a capital offence - Dudai, Ron (The British journal of criminology, 2021)
This article explores the causes, forms and consequences of the resilience of treason as a capital offence. Though generally overlooked by the literature on the death penalty, treason has been the second most common capital offence—after murder—in states’ law books in the post-WWII world and has had tangible effects on abolition trajectories. The article first traces the transformation of treason from the paradigmatic capital offence in the pre-modern era to a peripheral yet persistent component of contemporary death penalty. It then analyses and explains the dynamic of ‘exempting’ treason from abolition for common crimes. The third section examines situations where treason remains a capital offence on the books but is rarely used, functioning as ‘symbolic law’ with important consequences and spillover effects. In the conclusion, I argue that treason laws could become a central obstacle in the path to full global abolition of the death penalty.